Analysis of School Food Safety Programs Based on HACCP Principles - Roberts, Kevin R.; Sauer, Kevin L.; Sneed, Jeanie; Kwon, Junehee; Olds, David; Cole, Kerri; Shanklin, Carol W. (My University, 2016)
Purpose/Objectives: The purpose of this study was to determine how school districts have implemented food safety programs based on HACCP principles. Specific objectives included: 1. Evaluate how schools are implementing components of food safety programs and 2. Determine foodservice employees food-handling practices related to food safety. Methods: The study included a national sample of 34 school districts in eight states, including 11 small, 9 medium, 6 large, and 8 mega districts. Six researchers collected data on-site in each of the school's food production facilities. Data collection instruments included a Facility Observation Form, a Food Safety Observation Form, and a Hazard Analysis Critical Control Points (HACCP) Verification Checklist. All instruments were pilot tested prior to use. The research protocol was reviewed and approved by the University's Institutional Review Board prior to data collection. Data were summarized using descriptive statistics. A recent health inspection report was collected from each school and qualitative data were also compiled. Results: Of 34 schools visited, food safety plans were available in 33 schools, although few were customized to the specific school. Most of the recommended standard operating procedures related to HACCP were used. However, researchers found few records of corrective actions. The health inspection scores for most schools were high, which reflects that food safety practices had been adequately operationalized. Overall, school facility observations were positive. Approximately 60% of employees failed to wash their hands as recommended by the 2009 Food Code. Most employees washed their hands before preparing food, but many times, improper hand washing procedures were used. Applications to Child Nutrition Professionals: School foodservice employees performed well, but there are opportunities for food contamination to occur. Directors and managers can utilize this data to evaluate their food safety programs and practices to assure they are achieving their intended goal to serve safe and wholesome food to schoolchildren.
Citation: Roberts, K., Sauer, K., Sneed, J., Kwon, J., Olds, D., Cole, K., & Shanklin, C. (2014). Analysis of school food safety programs based on HACCP principles. Journal of Child Nutrition and Management, 38(1).
Keywords: HACCP; Food Safety; School Foodservice; Employee Behaviors; Facility